Nutrient intake and environmental enteric dysfunction among Nepalese children 9–24 months old—the MAL-ED birth cohort study. (October 2018) - Morseth, Marianne; Strand, Tor; Torheim, Liv; Chandyo, Ram; Ulak, Manjeswori; Shrestha, Sanjaya; Shrestha, Binob; Henjum, Sigrun
Abstract Background Nutrient deficiencies limit the growth and turnover of intestinal mucosa, but studies assessing whether specific nutrients protect against or improve environmental enteric dysfunction (EED) are scarce. We aimed to investigate associations between nutrient intake and EED assessed by lactulose:mannitol (L:M) ratio, anti-1-antitrypsin, myeloperoxidase (MPO), and neopterin (NEO) among children 9–24 months in Bhaktapur, Nepal. Methods Among 231 included children, nutrient intake was assessed monthly by 24 h recalls, and 3-month usual intake was estimated using Multiple Source Method. Associations between nutrient intake and L:M ratio (measured at 15 months) were assessed using multiple linear regression, while associations between nutrient intake and fecal markers (measured quarterly) were assessed using Generalized Estimating Equations (GEE) models. Results We found that associations between nutrient intake from complementary food and L:M ratio, alpha-1-antitrypsin (AAT), MPO and NEO were generally negative but weak. The only significant associations between nutrient intake (potassium, magnesium, phosphorous, folate, and vitamin C) and markers for intestinal inflammation were found for MPO. Conclusion Negative but weak associations between nutrient intake and markers of intestinal inflammation were found. Significant associations between several nutrients and MPO might merit further investigation.